A systematic review and exploration of clinical application of liver depression syndrome in breast cancer - Wu, Peng; Mao, Siying; Zuo, Qian; Guo, Qianqian; Chen, Qianjun (Frontiers in Oncology, 2025)
Breast cancer remains one of the most prevalent malignancies among women. Traditional Chinese Medicine (TCM) identifies Liver depression syndrome as a core clinical pattern in breast cancer; however, the absence of systematic reviews addressing this specific syndrome has constrained the development and application of TCM interventions. This systematic review searched seven Chinese and English databases, and was supplemented by published books and clinical guidelines, to identify literature documenting TCM diagnostic indicators of Liver depression syndrome in breast cancer. The collated data formed the TCM item for Liver depression syndrome in breast cancer, and descriptive statistics were applied to analyze symptom patterns. This study revealed 104 distinct clinical manifestations and 56 tongue-pulse indicators. The predominant syndrome subtypes included syndrome of qi stagnation due to Liver depression (30.5%), syndrome of phlegm congealing due to Liver depression (24.7%), syndrome of Liver qi depression (19.7%), and syndrome of Liver depression and Spleen deficiency (15.6%). Key clinical manifestations comprised distending pain in the chest and sub-costal region (68%), depression (67%), breast mass (64%), anger (52%), breast distending pain (44%), and oppression in chest (44%). The most prevalent tongue manifestation was thin white fur, while the most common pulse pattern was the stringy pulse. The current findings highlight diagnostic inconsistencies in the definition of Liver depression syndrome in breast cancer, posing challenges to clinical research and the elucidation of syndrome mechanisms. Future investigations should prioritize the standardization and objective characterization of diagnostic criteria to enhance the accuracy of syndrome recognition and facilitate scientific validation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024546784.